2011
DOI: 10.1111/j.1479-8298.2010.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Ant community structure under Retama sphaerocarpa shrubs in a semi‐arid environment

Abstract: The Tabernas Desert (Spain) is an emblematic area as it constitutes, strictly speaking, the only European desert. Under the canopy of one of the dominant shrub species, Retama sphaerocarpa, there are different microhabitat conditions that encourage the growing of a dense understory of herbs (fertile islands). However, these changes may not be enough to be also reflected in the fauna. Studying ants as bioindicators, we found higher densities of individuals and species richness below the canopy than outside it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(62 reference statements)
1
6
0
Order By: Relevance
“…These results suggest that maximum temperatures or diurnal temperature variations can be used as cues to detect safe sites for the biota under the canopy. For example, Retana and Cerda (2000) noticed that ant communities track spatial and temporal variability in the thermal environment and reached the similar conclusions as above Carpintero et al (2011). Accordingly, the amelioration of the thermal environment produced by the patchy shrubs plays an important role in the under-canopy biota in desert ecosystems.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…These results suggest that maximum temperatures or diurnal temperature variations can be used as cues to detect safe sites for the biota under the canopy. For example, Retana and Cerda (2000) noticed that ant communities track spatial and temporal variability in the thermal environment and reached the similar conclusions as above Carpintero et al (2011). Accordingly, the amelioration of the thermal environment produced by the patchy shrubs plays an important role in the under-canopy biota in desert ecosystems.…”
Section: Discussionsupporting
confidence: 59%
“…Additionally, shading by shrubs provides shelter for insects, reptiles and other organisms in hot summer months. For instance, by studying ants as bioindicators in the Tabernas Desert, Carpintero et al (2011) reported higher densities of individuals and species richness under shrub canopy than in the interspaces, and pointed out that lower soil temperature beneath canopy may be the main factor. The soil surface temperature measurements made in the present study also showed that aspect of shrub strongly affected soil surface temperature heterogeneity around the shrub.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures may provide increased niche availability, a more stable environment, and increased moisture retention that all strongly influence the distributions of many other organisms (Pollet and Grootaert 1996;Sarig et al 1999;Finke and Snyder 2008;Carpintero et al 2011;Schirmel and Buchholz 2011). All known functional groups of ants can be found in the coastal dunes with the exception of Specialist Predators.…”
Section: Odontomachus Haematodus Xmentioning
confidence: 99%
“…Large scavenging ants, such as Cataglyphis spp. , locate their nests in open sites, which reduces competition with more dominant ant species [ 68 , 69 ]. In our study site, M. ebeninus and some dominant omnivorous ant species ( Tapinoma and Monomorium spp.…”
Section: Discussionmentioning
confidence: 99%